2015
DOI: 10.1177/1046496415570916
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Diversity to Team Outcomes

Abstract: Effects of diversity in team members' rational and intuitive cognitive styles on team outcomes were investigated in a moderated-mediation model, exploring conflict management as a moderator and cohesion as a mediator. The negative effects of diversity on cohesion were moderated by conflict management, such that diversity harmed cohesion when conflict management was low but had no effect when conflict management was high. Cohesion mediated the relationship between the interaction of cognitive diversity and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…Our results suggest that the benefit of this diversity is particularly pronounced in situations where teams are encouraged to reflect deeply and intentionally on their experiences, goals, and past performance. Some work suggests that team diversity can have negative effects (e.g., by inducing team conflict; Curseu and Schruijer, 2008;Mello and Delise, 2015); thus, managers must balance the informational benefits of diversity against the benefits of harmony that can arise from more homogenous teams.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Our results suggest that the benefit of this diversity is particularly pronounced in situations where teams are encouraged to reflect deeply and intentionally on their experiences, goals, and past performance. Some work suggests that team diversity can have negative effects (e.g., by inducing team conflict; Curseu and Schruijer, 2008;Mello and Delise, 2015); thus, managers must balance the informational benefits of diversity against the benefits of harmony that can arise from more homogenous teams.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…A network of contacts represents potential resources-an individual needs to become active and ask for feedback to actually access these resources (Ashford & Cummings, 1985;Frieling & Froehlich, 2017;Harwood & Froehlich, 2017). One important mechanism here is homophily-the tendency to build relationships with similar others (McPherson et al, 2001;Mello & Delise, 2015). Previous research offers two theoretical explanations for this tendency.…”
Section: Developing Competence-based Employability Via Seeking Feedbackmentioning
confidence: 99%
“…Other studies have found interaction effects between cognitive style diversity and team affective processes. For example, Mello and Delise (2015) found that diversity in rational-intuitive styles reduced cohesion but only when conflict management was low. Mello and Delise’s results were consistent with Volkema and Gorman’s because they found no direct cognitive style diversity effects on performance (objective).…”
Section: An Organized Review Of the Literaturementioning
confidence: 99%